Pharmacogenomic Approaches to Asthma Treatment - Cho, Sang-Heon (The Korean Academy of Asthma, Allergy and Clinical Immunology; The Korean Academy of Pediatric Allergy and Respiratory Disease, 2010)
Major classes of medication in asthma management include bronchodilating β2-agonists, anti-inflammatory inhaled corticosteroids, leukotriene modifiers and theophyllines. However, all asthmatics do not respond to the same extent to a given medication. Available data suggest that a substantial range of individual variability, as much as 70%, may be due to genetic characteristics of each patient. Pharmacogenomics offers the potential to optimize medications for individual asthmatics by using genetic information to improve efficacy or avoid adverse effects. The best-studied case of the potential contribution of pharmacogenomics to treatment response in asthma comes from studies on human β2 adrenergic receptors. In addition, genetic variation in β2-adrenergic receptor (Arg16Gly) may predict response to anticholinergics for the treatment of asthma. In case of inhaled corticosteroids, a recent investigation using a traditional SNP-based approach identified a gene for corticotropin releasing hormone receptor 1 as a potential marker of response. Another major pathway that has been investigated is the pathway underlying response to cysteinyl leukotriene receptor antagonist. It is likely that in the near future, pharmacogenomic approaches based on individual genetic information will be introduced into an asthma treatment guideline and this guideline will allow us to identify those who have the best chance to respond to a specific medication.